Satisfaction with Nighttime Outdoor Activity Environment Among Elderly Residents in Old Gated Communities - Fang Wen; Liang Peng; Bo Zhang; Yan Zhang; Yuyang Zhang (Buildings)
China, like many other countries around the world, faces a rapidly aging population. “Aging in place” is the most popular choice for older people in China, with more than 90% of urban older people living in the same residential areas they did in middle age. Nighttime outdoor activity (NOA) is popular among the elderly and has a positive impact on both their physical and mental health. However, the conditions of nighttime activity places in old gated communities often do not meet the activity needs of the elderly, and there are problems such as low lighting and poor accessibility. This study focuses on typical old gated communities in a large city and analyzes data on three dimensions of independent variables: the lighting of activity places, the built environment of old gated communities, and the attributes of the elderly residents themselves. Taking “satisfaction with the environment for NOAs”, “the biggest environmental problem with NOAs”, and “locations that need improved lighting” as dependent variables, we used machine learning to calculate the contributions of various influencing factors on the dependent variables. It was found that the most important factors that influence satisfaction with the NOA environments are lighting levels, with the built environment or elderly residents’ attributes being less important. The most important factor that influences older people’s judgment of “locations that need improved lighting” is the perception of safety related to lighting in NOAs, followed by the perception of uniform lighting and green areas in their gated community. This study provides a reference for the renovation of age-friendly community environments as well as the overall enhancement of the nighttime activity environments in old gated communities.